Análise da integração dos médicos cubanos do Programa Mais Médicos para o Brasil de 2013 a 2016 - Feitosa, Alexsandra Moreira (2017)
This dissertation aims at analyzing how the Cuban doctors contacted in an inter-national cooperation scheme were associated with the Pan American Health Organization, the Brazilian government and the Cuban government to work in the Program of Medical Doctors of the Federal Government. Emphasizing that the hiring of foreigners, especially Cubans, was one of the main points of divergence in relation to public policy, raising questions about the organization of public health in Brazil and the organization of the Brazilian medical class as a united category in claiming their interests. The objective was to analyze how these professionals were able to enter Brazilian territory and how this impacted the work within the Program. Also as from the contact with other social actors, patients, Brazilian doctors, work team, etc. was being built the figure of this foreigner, taking into account social political aspects and above all the fact that he falls into the category of qualified and temporary migrant. The time frame of the study is mentioned between the years of 2013, with the beginning of the Program and 2016, when they closed the first contacts of foreigners. The methodology adopted consisted of a qualitative approach focused on the analysis of the reports collected by the interviewees from the interviews conducted in the form of focus groups held in the states of Minas Gerais, Rio de Janeiro and São Paulo.